The association between hip dysfunction and lower limb injuries in long-distance runners: a systematic review - Tau, Monica (My University, 2018)
Background Running is an inexpensive popular sport with growing participation worldwide. Running is generally associated with improved overall health but it also yields a significant risk of sustaining running-related musculoskeletal injuries. The association between hip dysfunction and lower limb injuries sustained in long-distance runners is not clear; therefore, a systematic review to clarify this association was needed. The objective of this review was to assess the association between hip dysfunction and lower limb injuries in long-distance runners. Method Studies that included participants who were 18 years of age and older, long-distance runners and injury-free at the time of the study, were included in this systematic review. Runners had to have participated at all levels of performance and be followed up for a period of one month or more. Studies that investigated hip dysfunction as an independent variable were included. Hip dysfunction entails poor hip muscle strength, poor hip control, excessive or limited range of motion, mal-alignment of the hip, and poor hip-running mechanics, but is not limited to the abovementioned. Lower limb injuries, which include any non-contact injuries of the lower limb, were considered to be the independent variable in this study. Such injuries needed to have been evaluated by health-care providers. However, lower limb injuries that were reported by the participants in this research project were also included in the study. Furthermore, only prospective and retrospective longitudinal cohort studies were included in this systematic review. A search strategy using the key words “running”, “hip”, and “lower limb injury” was undertaken. The following databases were searched from inception to June 2017: MEDLINE via PubMed, Cumulative Index to Nursing and Allied Health Literature (CINAHL), ProQuest Health, EBSCO MasterFile Premier, Physiotherapy Evidence Database (PEDro), Science Direct, PROSPERO, SCOPUS and SPORTDiscus, all with full text. Unpublished studies were searched on EBSCO MasterFile Premier Prospective, and observational, longitudinal cohort studies were included in the systematic review. The methodological quality was assessed using the Joanna Briggs Institute’s Critical Appraisal Checklist for Comparable Cohort/ Case Control Studies. A standardised data extraction tool from the Joanna Briggs Institute MAStARI was also used to extract data from the included studies. Results Eight studies were included in the systematic review. Seven studies were prospective cohort studies and one study was a retrospective cohort study. One study was a dissertation and the remaining seven studies were peer-reviewed articles. No meta-analysis of findings could be performed on account of the heterogeneity of the studies. As such, the findings were analysed in narrative form. The main hip dysfunction factor studied in long-distance runners was found to be the hip adduction angle and the hip abduction moment. The hip adduction angle in female long-distance runners was considered to be a risk factor for developing patellofemoral pain (p=0.007) and iliotibial band syndrome (p=0.01). The active straight leg raise test is one of the tests of the Functional Movement screen test that was found to be predictive of running-related injuries in males (p=0.01). Moreover, it was noted that the composite score of the Functional Movement screen test is not predictive of running-related injuries (p=0.10). Conclusion There were methodological differences between the studies, mainly in terms of defining and measuring running-related injuries. It was found that an increased hip adduction angle in female runners is associated with patellofemoral pain and iliotibial band syndrome. Functional tests such as the active straight leg raise test may possibly be used to screen male athletes for running-related injuries.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Science in Physiotherapy to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, 2018